Folk song conservation strategies from a cross-cultural perspective: a systematic literature review - Liu, Guangchao; Lee, Yok Fee; Ab. Razak, Ratna Roshida; Ab. Majid, Arfah (Human Resource Management Academic Research Society, 2024)
This article uses a systematic literature review to deeply explore the core elements, challenges, and effectiveness of folk song conservation strategies around the world. As an important carrier of cultural heritage and community identity, folk songs face many challenges in modern society, including adaptation to cultural modernization, insufficient financial resources, and a lack of inheritance talents. This study focuses on analyzing and summarizing specific strategies and measures that can effectively promote and protect this unique cultural form. On this basis, we further explored the role of community action in folk song preservation, that is, how different communities support the preservation and inheritance of folk songs through participation and cooperation. The literature review shows that government support, the formulation and enforcement of cultural heritage regulations, education and training programs, and the application of modern technology in cultural inheritance are the main strategies for folk song preservation. In addition, community participation plays an important role in the revitalized inheritance and daily practice of folk songs. The role of governments and institutions is to provide the necessary support and protective framework to promote the continuity and vitality of folk song culture. This study aims to provide theoretical support and practical reference for future research and practice in the field of folk song protection.